Entangled coercion African and indigenous labour in Charcas (16th-17th century) - Revilla Orías, Paola A. (Work in global and historical perspective, 2020)
This book investigates the phenomenon of slavery and other forms of servitude experienced by people of African or indigenous origin who were taken captive and then subjected to forced labor in Charcas (Bolivia) in the 16th and 17th centuries.